Three-dimensional hydrodynamic modelling using two-dimensional mesh: application to flows in curved channels. Issue 2 (4th March 2017) - Meftah, Khouane
ABSTRACT: To model free-surface flows, a three-dimensional model is developed using a new approach where the horizontal velocity components are projected onto a basis of functions depending on the vertical coordinate z . The choice of this basis and the number of its terms depend on the physical problem and the desired precision. The vertical velocity component and the non-hydrostatic pressure are analytically determined. The integration of the variational form of main flow equations with an adequate choice of test functions transforms the three-dimensional model in a two-dimensional model. The finite element method using a two-dimensional mesh is used to solve the problem. This model is stable and robust because it does not use a mesh in the vertical direction. It is also accurate as the functions that best fit the physical nature of the flow can be directly introduced. The application of the proposed model to flows in curved channels is given.